EFFECTIVENESS OF COURT-ANNEXED MEDIATION IN JOINT PROPERTY DISPUTES: EVIDENCE FROM THE MAKASSAR RELIGIOUS COURT - Dewi Sartika (UIN Palopo, 2026)
The increasing number of joint property disputes following divorce has highlighted the importance of mediation as an alternative dispute resolution mechanism within the Religious Courts. Despite its mandatory implementation under Indonesian procedural law, the effectiveness of mediation in resolving joint property disputes remains questionable. This study aims to analyze the effectiveness of mediation in joint property cases at the Makassar Religious Court in 2024 and to identify the factors supporting and hindering its implementation. This research employed a qualitative descriptive design using an empirical juridical approach. Data were collected through observations, semi-structured interviews with judge-mediators and court officials, and analysis of court documents concerning joint property cases. The collected data were analyzed descriptively by relating empirical findings to the legal effectiveness framework proposed by Soerjono Soekanto. The findings reveal that mediation has been effectively implemented procedurally, as 20 of 24 cases (83.33%) underwent mediation in accordance with Supreme Court Regulation No. 1 of 2016. However, substantive effectiveness remains limited, with only six cases (25%) successfully reaching settlement agreements, while most disputes proceeded to litigation. The study further identifies that mediator professionalism, the parties' good faith, adequate mediation facilities, and a culture of deliberation constitute the principal factors supporting successful mediation. Conversely, post-divorce emotional conflicts, the high economic value of disputed assets, lack of good faith, litigation-oriented legal representation, and the perception of mediation as a mere procedural formality significantly impede its effectiveness. These findings suggest that improving mediator competencies, strengthening public understanding of mediation, and promoting a legal culture favoring consensual dispute resolution are essential to enhancing the effectiveness of mediation in joint property disputes within the Religious Courts.